The influence of whole-body vibration on creatine kinase activity and jumping performance in young basketball players - Fachina, R.; da Silva, A.; Falcão, W.; Montagner, P.; Borin, J.; Minozzo, F.; Falcão, D.; Vancini, R.; Poston, B.; de Lira, C. (Research Quarterly for Exercise and Sport, 2013)
Purpose: To quantify creatine kinase (CK) activity changes across time following an acute bout of whole-body vibration (WBV) and determine the association between changes in CK activity and jumping performance. Method: Twenty-six elite young basketball players were assigned to 3 groups: 36-Hz and 46-Hz vibration groups (G36 and G46, respectively) and a control group. The study quantified CK activity and jumping performance following an acute bout of WBV at 2 vibration frequencies. Both WBV groups performed a protocol that consisted of 10 sets of 60 s of WBV while standing on a vibration plate in a quarter-squat position. CK activity, countermovement jumps (CMJ), and squat jumps (SJ) were measured immediately before and 24 hr and 48 hr after WBV. In addition, CMJ and SJ were also measured 5 min after WBV. Results: CK activity was statistically significantly increased 24 hr following WBV in G36 and G46. At 48 hr after WBV, CK activity was similar to baseline levels in G36 but remained statistically significantly above baseline levels in G46. The CMJ and SJ heights were statistically significantly decreased at 5 min following the protocol for both WBV groups. Overall, the changes in CK activity did not present a strong relationship with the changes in jump heights for any of the comparisons. Conclusions: These findings suggest that WBV protocols with such characteristics may not cause excessive muscle damage and may partly explain why many WBV training studies have failed to elicit increases in strength performance.